PELAKSANAAN TUGAS SATUAN POLISI PAMONG PRAJA (SATPOL PP) DAN PEMADAM KEBAKARAN (DAMKAR) DI KABUPATEN SIJUNJUNG - Sinta Westika Putri; Eva Suryany; Ulil Amri (Jurnal Public Administration, Business and Rural Development Planning, 2021)
The purpose of this research is to find out the implementation of the duties of the Civil Service Police Unit (Satpol PP) in Organizing Public Order and Peace in Sijunjung Regency, the obstacles faced in implementing the Duties of the Civil Service Police Unit (Satpol PP) in Organizing Public Order and Peace in Sijunjung Regency, and the efforts made in overcoming obstacles to implementing the Duties of the Civil Service Police Unit (Satpol PP) in Organizing Public Order and Peace in Sijunjung Regency. This type of research is qualitative research with descriptive methods. The results showed the implementation of the duties of the Civil Service Police Unit (Satpol PP) and the Fire Department (Damkar) in Sijunjung Regency. Implementing the duties of the Civil Service Police Unit (Satpol PP) in Sijunjung Regency comprises enforcing Regional Regulations and Regional Regulations, maintaining public peace and order, and implementing community protection. The obstacle faced is that there are still many people who do not understand the regulations contained in the regional regulations. And officers have difficulty moving because there is no minimum service standard. Efforts are being made to overcome the obstacles, namely to socialize and provide guidance to the community about public order regulations. And the need for an institutional development that is able to support the realization of peace and order.